2017
DOI: 10.1002/rcm.7810
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of on‐line hydrogen stable isotope ratio measurements of halogen‐ and sulfur‐bearing organic compounds using elemental analyzer–chromium/high‐temperature conversion isotope ratio mass spectrometry (EA‐Cr/HTC‐IRMS)

Abstract: The optimized EA-Cr/HTC reactor design can be implemented in existing analytical equipment using commercially available material and is universally applicable for both heteroelement-bearing and heteroelement-free organic-compound classes. The sensitivity and simplicity of the on-line EA-Cr/HTC-IRMS technique provide a much needed tool for routine hydrogen-isotope source tracing of organic contaminants in the environment. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…We stress that this offset is relevant for bone collagen only, since other N‐containing and halogen‐ and sulfur‐containing materials have somewhat different δ 2 H values in Cr‐packed vs glassy‐C‐packed reactors.…”
Section: Discussionmentioning
confidence: 98%
“…We stress that this offset is relevant for bone collagen only, since other N‐containing and halogen‐ and sulfur‐containing materials have somewhat different δ 2 H values in Cr‐packed vs glassy‐C‐packed reactors.…”
Section: Discussionmentioning
confidence: 98%
“…The conversion into H 2 gas was achieved with a high‐temperature furnace (Hekatech, Wegberg, Germany) held at 1430°C that was equipped with a glassy carbon tube inside a silicon carbide tube (tube in tube design) with a reverse feed He carrier gas flow rate of ~80 mL/min. Gehre et al and Nair et al have shown that the HTC reactor should be filled with chromium when measuring the δ 2 H signature of heteroatom (N, S, F, Cl, Br, I)‐containing compounds. Chromium traps the heteroatoms and thus facilitates a quantitative conversion of analyte into H 2 gas, and subsequent transport to the isotope ratio mass spectrometer .…”
Section: Methodsmentioning
confidence: 99%
“…The general trend was to move towards carbon‐based reactors, but as far as halogenated compounds have been concerned, this option could not be retained in the case of salts . Thus, we used a modified Cr‐based reactor to optimize 2 H/ 1 H measurements of aqueous inclusions trapped in halite.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][23][24][25][26][27] The general trend was to move towards carbon-based reactors, but as far as halogenated compounds have been concerned, this option could not be retained in the case of salts. 13,14 Thus, we used a modified Cr-based reactor to optimize 2 H/ 1 H measurements of aqueous inclusions trapped in halite. In order to evaluate our technique, we generated "synthetic" halite crystals precipitated from a water reservoir where the 2 H/ 1 H ratio was monitored throughout the course of its evaporation from the initial stage until complete crystallization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation